Interatrial communication and pulmonary hypertension in a hematologic patient - Gon, Renata Peixoto Abrão; Santos, Vitória Rossetti Moreira dos; Lemes, Dara Ramires; Stradiotto , Diogo (Research, Society and Development, 2025)
Atrial Septal Defect (ASD) is a congenital malformation classified into four types: secundum, primum, venous sinus, and coronary sinus, with the first being the most prevalent and the focus of this investigation. The diagnosis of this condition is of fundamental importance due to its potential complications, which can be exacerbated when associated with other comorbidities such as sickle cell anemia and chronic myeloid leukemia (CML), which deserve special consideration, especially if the treatment involves cardiotoxic agents. The objective of this descriptive study is to emphasize the complexity of the clinical approach to congenital heart diseases and hematologic disorders through a case report accompanied by a relevant literature review. Based on the analysis of a unique case, using data obtained from the electronic medical record, the report highlights a 57-year-old white female patient, married and with a domestic occupation, seeking medical assistance due to symptoms of post-exercise dyspnea and persistent fatigue. The patient was on second-line treatment for chronic myeloid leukemia (CML), using Dasatinib for 5 months. A transthoracic echocardiogram was performed, revealing the presence of ASD and consequent pulmonary hypertension (PH), which may have been exacerbated by the use of the chemotherapeutic agent, considering that PH is a known adverse effect of the medication as described in the literature. The conclusion of this study reinforces the importance of a comprehensive, interdisciplinary, and personalized approach for early diagnosis, in order to optimize therapy accurately and ensure the patient's quality of life.